Pengaruh Job Insecurity Terhadap Loyalitas Pegawai dan Guru Pada SMP PGRI 9 Denpasar dengan Kepuasan Kerja Sebagai Variabel Mediasi - Agung Widya; Ni Putu Putri Ayu Wijayanthi; Komang Ary Pratiwi; Ni Kadek Muliati (Widya Manajemen, 2023)
Loyalty to work is a binding condition between an employee and an agency or company. Problems with this study are: SMP PGRI 9 How does job insecurity in Denpasar affect employee retention? SMP PGRI 9 How does job satisfaction affect employee retention in Denpasar? SMP PGRI 9 How does job insecurity in Denpasar affect job satisfaction? What role does satisfaction play? The purpose of the study was to analyze the effect of job insecurity on employee retention. Analysis of the impact of job satisfaction on employee retention. Analysis of the impact of job anxiety on job satisfaction. Analyze the role of job satisfaction in mediating the effects of job insecurity on employee loyalty. It is analyzed with classical acceptance tests, path analysis, and Sobel tests. The results showed that employment instability has a positive and significant impact on employee retention. Job satisfaction has a significant positive impact on employee retention. Job instability has a significant positive impact on job satisfaction. Job satisfaction tells the impact of job instability on employee loyalty.